Coupled magneto‐buoyant convection and radiation in an inclined enclosure: An exhaustive study. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – The current study aims to address the interaction between participating media radiation with thermo‐gravitational convection of an electrically conducting fluid enclosed within a tilted enclosure under an externally imposed time‐independent uniform magnetic field.Design/methodology/approach – The differentially heated boundaries of the tilted enclosure are considered to be diffuse, gray and the enclosed fluid is assumed to be absorbing, emitting and isotropically scattering. The Navier‐Stokes equations, meant for magneto convection are solved using modified MAC method. Gradient dependent consistent hybrid upwind scheme of second order is used for discretization of the convective terms. Discrete ordinate method, with S8 approximation, is used to model radiative transport equation in the presence of radiatively active medium.Findings – Effect of uniform magnetic field with different magnitudes and orientations of cavity has been numerically simulated. The effect of participating media radiation has been investigated for different optical thicknesses, emissivities, scattering albedos and Planks number. The results are provided in both graphical and tabular forms. The flow lines, isotherms bring clarity in the understanding of flow behaviour and heat transfer characteristics.Originality/value – Despite the idealized nature, the present study is quite essential to understand the cumbersome physics of realistic problem. Acknowledgements : The authors wish to acknowledge Prof. T. Sundararajan (IIT Madras), Prof. S.N. Panigrahi and Prof. P. Rath (IIT Bhubaneswar) for their advice, moral support and motivation.